The cinematic scenario in poems of Adonis and Charles Simic (a comparative study) - Al-Muqdadi, Dalal Ahmed Burhan; Toklubok, Pabiyah; Syed Abdullah, Syed Nurulakla (Usuli Faqih Research Centre, 2024)
The use of the cinematic scenario in the poems of Adonis and Charles Simic is considered one of the most important studies because the technique of the scenario penetrated into the poetic poem to give it something of the developments of the era and to reveal the mystery surrounding them. This research came to solve the problem of ambiguity in the poems of Adonis and Charles Simic and to prove the philosophy of the poem between thinking in the word and thinking in the image. This study aims to describe the use of cinematic script elements in the poems of Adonis and Charles Simic, to analyse the elements of cinematic script Adonis and Charles Simic use in their poems, and then to show the similarities and differences between Adonis and Charles Simic in their poems. This study relies on a comprehensive approach between the analytical-descriptive approach and the comparative approach. To analyse and compare the selected poems from the collections "Songs of Mihyar Al-Dimashqi" by Adonis and “My noiseless entourage" by Simic, the methodology of Mohammed Ajour was used. The results suggest that the poetic image in Adonis's poems has gained another literary form from the mechanisms of the scenario in addition to its basic form that supports the poetic significance in terms of revealing the mystery, while Simic's poetic image has benefited from the field of photography as a method that supports the disturbance of its psychological factor. As for the similarities and differences, the similarities lie in the growth, development, and search for everything new in content and form. The difference lies in the poetic structure and the attempt to create a new current, contemporary horizons, and visual methods that had not been explored before.